Physiotherapy Service without Documentation at a Community Based Rehabilitation for Children with Disabilities in Makassar City: A Case Study of Physiotherapist’s Perspective - Triana Karnadipa; Ari Nurfikri (Jurnal Sosial Humaniora Terapan, 2020)
This study aims to analyse the consequences of a lack of documentation in a community-based rehabilitation (CBR) unit for children with disabilities. 278 hours of observation and two structured interviews were conducted. Observation notes were depicted in a fishbone chart and interview findings were coded manually in a series of open, axial, and selective coding. The findings, field notes, and self-reflective notes were triangulated and link thematically. The findings revealed that failures to address children’s needs and progress, inability to modify the intervention based on evidence and lack of confidence in the therapists’ professionalism are the common problems experienced by the therapists due to lack of record-keeping. While the needs of CBR units are greatly increased for people with disabilities, CBR organisations and the Indonesia physiotherapy association need to cooperate in order to develop a clear clinical pathway and standardised documentation for a CBR context.